The Role of Tick Size in Upstairs Trading and Downstairs Trading - Griffiths, Mark D.; Smith, Brian F.; Turnbull, D.Alasdair S.; White, Robert W. (Journal of Financial Intermediation, 1998)
This paper examines the impact of reducing the tick size on market-making behavior on The Toronto Stock Exchange. The results indicate a significant decrease in the percentage of trades of fewer than 10,000 shares involving the upstairs traders and a significant increase in the percentage of trades of fewer than 1,000 share involving the designated market makers. Consistent with this finding, the upstairs traders earn significantly lower returns on non-block trades and the designated market markers earn lower returns on trades smaller than 1,000 shares. We conclude the tick size reduction benefits the trading public.Journal of Economic LiteratureClassification Numbers, G20, G24.